The Importance of Natural History in Wildlife Rehabilitation - Mannas, Jen (Wildlife Rehabilitation Bulletin, 2021)
Wildlife rehabilitation is unique in that it not only considers the welfare of wildlife communities but also the welfare of individual animals. One of the main goals of wildlife rehabilitation is to care for sick, injured and orphaned wild animals for the purpose of releasing them back to the wild. Many of the tens of thousands of wild patients rehabilitators treat each year are directly affected by humans; rehabilitation is seen as a way to mitigate that impact. The diversity of species treated is vast and it is important for wildlife rehabilitators and veterinarians to understand not only basic biology but also the natural history of these species. Nutritional requirements, behavior, habitat requirements, and social structure are just a few of the important natural history traits that help an animal survive in the wild. Understanding them will promote healing, reduce stress and facilitate successful rehabilitation.